Pengaruh Multiple Intelligences Pada Mata Pelajaran PAI Materi Fiqih Terhadap Hasil Belajar Siswa Kelas VIII SMPN Sumber Rejo Kabupaten Musi Rawas - Nuraini Nuraini; Joni Helandri; Yesi Arikarani (Edification Journal : Pendidikan Agama Islam, 2020)
A teacher's dilemma in implementing education is how to create learning innovations that aim to increase conceptual understanding. The multiple intelligences strategy can improve student learning outcomes and understanding and can also find some student intelligence to be more active and interactive. Experimental quantitative research approaches, One-group pre-test and post-test designs. The population is 81 students and the sample is class VIII.3 with 27 students. Data collection techniques are test techniques. t test analysis results with a level of confidence α = 0.05, obtained tcount (8.696)> ttable = 1.703 then Ha is accepted and Ho is rejected. So that it can be concluded that multiple intelligences strategy influences student learning outcomes in Islamic Religious Education subject matter of Fiqh (sunnah rawatib prayer) class VIII.3 SMPN Sumber Rejo Musi Rawas Regency.